ESG rating disagreement and bank loan availability: Evidence from China - Jidong Qin; Meijia Wang (PLoS ONE, 2025)
Environmental, social, and governance (ESG) ratings are receiving increasing attention in credit markets. However, ESG rating disagreement erects obstacles for companies in obtaining capital resources. This study investigates the impact of ESG rating disagreement on bank loan availability uses data of Chinese listed firms from 2014 to 2022, and employs models with multiple regression analyses and fixed effects. We find that greater ESG rating disagreement leads to a decrease in newly obtained bank loans. The mechanism analysis confirms that ESG rating disagreement amplifies information asymmetry and increases operational uncertainty, thereby raising the information and credit risks faced by banks, leading to a decrease in bank loan availability. Heterogeneity analysis reveals that the negative effect of ESG rating disagreement on bank loan availability is more pronounced in firms with poor financing capabilities, poor information environments, and fierce competitive macro environments. Our findings contribute to the literature on ESG rating disagreement from credit markets, which are important for a more comprehensive and objective understanding of ESG rating disagreement.